Diagnosis and phytoremediation proposal for wastewater treatment, black earth sector (Revista de Diavulgación L'esprit Ingénieux, 2020)
The project was born from the need to use water from the La Pinocha creek for the use of irrigated crops and pastures, and it is also broken down by dumping by the Puente de Boyacá path, specifically the Tierra Negra Sector, the lack Control in the dumping of contaminated water to surface water bodies in Colombia is one of the problems that affects the environment due to the fact that it does not establish the maximum permissible limit values, for this reason since March 17, 2015 in Colombia it was established Resolution 0631 which constitutes the maximum limit values for the discharges of contaminated water to surface water bodies. Indeed in Boyacá there is pollution of the rivers and streams of the department, for example the Pinocha stream which is being contaminated by discharges of domestic, industrial and institutional wastewater that comes from the black earth sector of the municipality of Ventaquemada, also the use that this water is receiving from the La Pinocha stream are not the correct ones since this flow is being used to irrigate crops, pastures and wash agricultural products.
Keywords: Shedding; Water bodies; Contamination; Environment; Flow